Child Prisoners and Their Attitudes: The Capture of Child Behavior Changes in Correctional Institutions - Steny Roby Waluya (Unnes Law Journal, 2021)
This study aims to determine how social learning changes the behavior of correctional students placed in correctional institutions. The method used in this research is a descriptive survey using a qualitative approach. Researchers conducted interviews with correctional students who were used as resource persons. Correctional students who are placed in Correctional Institutions absorb and follow most of the habits and activities carried out by adult prisoners who are in them, there are even correctional students who follow violations committed by adult prisoners so that after leaving the Correctional Institution they tend to do more evil. On average, they interact more with adult inmates so that they tend to learn everything that is in prison from adult inmates, including in terms of criminal behavior plans. After conducting research and interviews, it is known that the impact of social learning received by children when placed in an adult Correctional Institution is that children learn about positive and negative behavior carried out by friends in their social environment.